2012
DOI: 10.1038/jhg.2012.106
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of a lung cancer risk haplotype in the IL1B gene regulatory region

Abstract: Interleukin-1b (IL-1b), encoded by the IL1B gene, is a cytokine important in regulation of the inflammatory response. Elevated levels of IL1B expression have been associated with risk of gastric and lung cancer. We previously reported that a certain haplotype containing four single-nucleotide polymorphisms (SNPs) ( À3893G, À1464G, À511C and À31T; GGCT) in the IL1B gene regulatory region was associated with lung cancer risk and increased expression of the IL1B gene in the lung. In the present study, we have clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…In agreement, immunoblotting recorded a significant IL1B increase in PTK7, sPTK7 and Chz cells. An inflammatory IL1B cytokine is involved in cancer onset and progression [27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…In agreement, immunoblotting recorded a significant IL1B increase in PTK7, sPTK7 and Chz cells. An inflammatory IL1B cytokine is involved in cancer onset and progression [27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…High expression of some interleukins, such as IL-1α and IL-1β, has been associated with a more aggressive tumor type and poor prognosis [55-57]. ADSCs-SCCs-co-culture - both, with A431-SCCs and primary SCCs, led to a strong increase in IL-1α and β gene expression in ADSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, they provided evidence that 1L1B rs12621220 (-3893) GA and rs1143623 (-1464) GC in the enhancer region may also affect this risk and the four SNPs (G-3893A, G-1464C, T-511C, C-31T) formed a specific risk haplotype GGCT associated with increased IL1B gene expression [17]. They also showed that this haplotype have high transcriptional activity in the human lung epithelial A549 cell line in vitro [18]. A study in a Danish population showed that the carriers of the C allele of IL1B-31 were at higher risk of lung cancer than TT genotype [19].…”
Section: Introductionmentioning
confidence: 93%